The Effect Of The Role Of Parents On Learning Motivation In Based Learning Online Students In Pannara State Elementary Makassar City - Rianti, Rianti; Waddi Fatimah; Jusmawati; Bellona Mardhatillah Sabillah (Program Studi Pendidikan Agama Islam (PAI), 2022)
This study aims to determine the influence of the role of parents on learning motivation in online-based learning for Pannara Elementary School students, Makassar City. This research is classified as Ex post facto using a quantitative approach. This research was conducted at SD Negeri Pannara Makassar City using a questionnaire instrument. The sample in this study were all students of class VA and VB SD Negeri Pannara Makassar City which consisted of 66 students with simple random sampling technique. The results of the study using descriptive statistical analysis, the average value of the role of parents is 90.83 in the very role category and the average value of learning motivation is 90.03 in the highly motivated category. Inferential statistical analysis, normality test results 0.537 > 0.05 (normally distributed), homogeneity test results 0.079 > 0.05 (homogeneous), linearity results 0.597 > 0.05 (linear), hypothesis testing shows a sig value of 0.000, with Sig criteria (0.000) < (0.05). The conclusion in this study is that there is an influence of the role of parents on learning motivation in online Pannara Elementary School students, Makassar City.